The Relationship Of Online Learning With The Learning Results Of Students Of Class V Theme 8 : Hubungan Pembelajaran Daring Dengan Hasil Belajar Siswa Kelas V Tema 8 - Muhimmatur Rofiqoh; Fitria Wulandari (Academia Open, 2021)
This study aims to determine the relationship between online learning and student learning outcomes in class V Theme 8 at SDIT EL HAQ Buduran. The research method used is non-experimental quantitative. The population used was all fifth grade students of Al Hazen SDIT EL HAQ and the sample in this study was 28 students. Data collection techniques used in the form of a questionnaire (questionnaire) and student learning outcomes tests. Data collection techniques through Microsoft Forms. The instrument used in the questionnaire (questionnaire) using a Likert scale, as well as learning outcomes tests in the form of multiple choice tests. The results of the study were then analyzed using the data normality test, linearity test and product moment correlation. Based on the results of the analysis, it can be concluded that there is a relationship between online learning and the learning outcomes of class V Theme 8 students at SDIT EL HAQ Buduran. From the results of this study, it is in the category of having a fairly strong relationship.